1989
DOI: 10.3382/ps.0680596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetic Strain, Slow Versus Rapid-Feathering Maternal Genotype, and Cage Density on the Performance of Single Comb White Leghorns

Abstract: Two hatches involving 11,158 pullets from 22 Single Comb White Leghorn strain crosses were used in these experiments: 13 from rapid-feathering (k+/-) and 9 from slow-feathering (K/-) dams, some of which shared common genetic backgrounds; and all from 5 homozygous k+ sire types. Birds were grown intermingled within hatch, and were subsequently caged in two laying houses, one with 30.5 cm x 40.6-cm cages and the other with 40.6 cm x 30.5-cm cages, at densities of three or four birds/cage. Data were collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…In crosses with RF males, SF dams pass their K gene only to male progeny; female progeny are RF, i.e., k/w. Some breeders of commercial egg layer lines, however, experience lower productivity and high mortality thought to be associated with ALV infection in RF progeny from SF dams (Harris et al, 1984;Havenstein et al, 1989). It was subsequently shown that RF hens from Subgroup Esusceptible SF dams can be congenitally infected with EV21 (Smith and Fadly, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…In crosses with RF males, SF dams pass their K gene only to male progeny; female progeny are RF, i.e., k/w. Some breeders of commercial egg layer lines, however, experience lower productivity and high mortality thought to be associated with ALV infection in RF progeny from SF dams (Harris et al, 1984;Havenstein et al, 1989). It was subsequently shown that RF hens from Subgroup Esusceptible SF dams can be congenitally infected with EV21 (Smith and Fadly, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports showed that negative effects are associated with the presence of ev21 in the genome (Harris et al, 1984;Havenstein et al, 1989) and may be attributed to the production of infectious EV21 (Smith and Fadly, 1988). The present study shows that some rare RF birds may be ev21 positive.…”
Section: Discussionmentioning
confidence: 97%
“…The association between SF and £v21 in breeds other than WL should be studied, because WL feather-sexed layers often have lower productivity and higher mortality rates than comparable RF females (Harris et al, 1984;Havenstein et al, 1989). These characteristics may be related to the ev2\ locus that encodes an infectious virus, EV21, which induces tolerance to oncogenic ALV (Smith and Fadly, 1988).…”
Section: Introductionmentioning
confidence: 96%
“…For example, ALVE loci that are transcriptionally active cause decreases in some economically important traits such as egg production, egg weight, and egg specific gravity (Gavora et al, 1991). Moreover, slow-feathering birds that carry the ALVE-21 element have lower production and increased mortality compared with their normal-feathering counterparts (Havenstein et al, 1989). Again, it is important to point out that effects differ between loci and that each endogenous element impacts its host in a locus-specific manner.…”
Section: Introductionmentioning
confidence: 98%